Gingival Melanin Depigmentation: A Review and Case Report - Srivastava, Sumedha; Shrivastava, Trilok; Dwivedi, Shivani; Yadav, Pramod (Journal of Orofacial Research, 2014)
The color of the gingiva has a tremendous impact on the esthetics of the smile. Clinically gingival melanin hyper pigmentation is presented as ‘black gum’ which is a common esthetic problem especially for those who have gummy smile. Several attempts have been made for removal of gingival pigmentation by different techniques. Each technique had its own supremacy in efficiency and also draw back. In the present cases, an effort has been made to assess the procedure of melanin depigmentation using surgical scalpel technique.